Analisis Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja pada Industri Pembangkit Tenaga Listrik - Wiedy Fatika Putri Suhartono; Lia Amalia (Jurnal Syntax Admiration, 2024)
Positive sentiments and satisfaction experienced by an individual about their job are reflected in their job satisfaction. Due to the shifted variables affecting work fulfillment among people, organizational administration must pay extraordinary consideration. The reason for this investigation is to recognize factors affecting job satisfaction among workers within the control era industry, especially within the Suralaya PGU Work Unit. Inspecting was conducted utilizing a purposive examining strategy including the cooperation of 205 respondents. Essential information was obtained through the utilization of surveys, and the Auxiliary Condition Modeling Fractional Slightest Squares (SEM PLS) method was utilized to analyze the information. The discoveries of this inquiry demonstrate that motivation and work fulfillment play a positive part in representative execution, whereas the work environment encompasses a positive effect on the level of work fulfillment. In any case, the work environment does not essentially impact representative execution, and inspiration does not have a significant effect on the level of work fulfillment. Furthermore, it was found that the level of work satisfaction can be a critical go-between within the relationship between the work environment and representative execution but does not play a critical intervening part in the relationship between inspiration and worker execution. The results of this research, it is expected to contribute significantly to human resource development and employee performance improvement, providing a valuable foundation for organizational management policies.